2005
DOI: 10.1002/smi.1058
|View full text |Cite
|
Sign up to set email alerts
|

The factorial structure of the GHQ‐12

Abstract: This paper studies the factorial structure of the 12‐item version of the General Health Questionnaire (GHQ‐12), Dutch translation, in a large Belgian sample (n = 9442) that is representative of the general population. Data was collected from the 2001 Belgian Health Interview Survey. In total, 11 factor‐structure models are tested by means of confirmatory factor analysis. Two models, a two‐factorial model without cross‐loadings and a three‐factorial model with cross‐loadings, prove to have acceptable model‐fit.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 16 publications
2
13
0
Order By: Relevance
“…Amongst all factor models being evaluated, the unitary (single factor) model was found to be the poorest fit to the data. These findings are consistent with previous studies suggesting that the GHQ-12 is a multi-dimensional scale that measures several distinct aspects of distress, rather than unidimensional measure of a general construct (Vanheule & Bogaerts 2005, Ip & Martin 2006.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Amongst all factor models being evaluated, the unitary (single factor) model was found to be the poorest fit to the data. These findings are consistent with previous studies suggesting that the GHQ-12 is a multi-dimensional scale that measures several distinct aspects of distress, rather than unidimensional measure of a general construct (Vanheule & Bogaerts 2005, Ip & Martin 2006.…”
Section: Discussionsupporting
confidence: 92%
“…Most importantly, the factor structure of GHQ-12 examined by previous studies was inconsistent (Vanheule & Bogaerts 2005, Ip & Martin 2006. 11 factors structure models were evaluated by means of confirmatory factor analysis based on data in a large Belgian sample, Vanheule and Bogaerts (2005) revealed that the two-factorial model (eight-item) developed by Kalliath et al (2004) is the best fitting model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The GHQ-12 is a widely used measure of psychological strain that has consistently reported high levels of internal reliability in previous studies (Ip & Martin, 2006;Vanheule & Bogaerts, 2005). Kalliath et al (2004) conducted a confirmatory factor analysis of the GHQ-12 and found that a two-factor model provided the strongest fit with data.…”
Section: Psychological Strainmentioning
confidence: 97%
“…Psychometric properties and especially dimensionality of the GHQ‐12 are still under debate. Although the GHQ‐12 was originally designed as a unidimensional measure, several one‐, two‐ or three‐factor solutions have been found across different studies (Werneke et al, ; Rey et al, ; Gureje, ; Kalliath, O'Driscoll, & Brough, ; Picardi, Abeni, & Pasquini, ; Politi, Piccinelli, & Wilkinson, ; Schmitz, Kruse, & Tress, ; Toyabe et al, ; Vanheule & Bogaerts, ; Hankins, ; Romppel, Braehler, Roth, & Glaesmer, ). The impact of methodological aspects on the factorial structure of the GHQ‐12 has been discussed in recent years (Rey et al, ; Hankins, ; Romppel et al, ).…”
Section: Introductionmentioning
confidence: 99%